Disseminated peritoneal coccidioidomycosis in pregnancy following fertility treatment: A case report and literature review - Armstrong Abigail; Watanabe Mika; Bhattacharya Debika; Zakhour Mae; Kroener Lindsay (Elsevier, 2021)
Disseminated peritoneal coccidioidomycosis in the setting of early pregnancy after fertility treatment is rare and can present as a diagnostic challenge. A 39-year-old underwent ovarian stimulation with clomiphene citrate followed by HCG trigger and intrauterine insemination. She developed persistent abdominal pain, ascites and episodes of fever in early pregnancy, and eventually underwent a diagnostic laparoscopy for worsening clinical presentation. Operative findings were notable for peritoneal studding, infracolic omentum inflammation, bowel adhesions to the abdominal wall and normal-appearing uterus and adnexa. The pathology results indicated peritoneal Coccidioides immitis infection. Hormonal changes associated with fertility treatment and immune tolerance in pregnancy may increase the risk for disseminated peritoneal coccidioidomycosis. A high index of suspicion and a multidisciplinary team are important for the diagnostic workup and treatment plan of disseminated peritoneal coccidioidomycosis.